2015
DOI: 10.1074/jbc.m114.633800
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Interactions between a Naturally Primed Immunoglobulin A and Its Conserved Bacteroides thetaiotaomicron Species-specific Epitope in Gnotobiotic Mice

Abstract: Background: IgA responses are important for human gut mucosal barrier function. Results: Gnotobiotic Rag1Ϫ/Ϫ mice harboring a human gut bacterial symbiont and a single, naturally primed IgA revealed species/strain/epitope level specificities and biological effects of the antibody. Conclusion: Bacteroides thetaiotaomicron maintains a highly conserved immunogenic epitope important for its fitness in vivo. Significance: Our approach can yield diagnostic antibodies and new understanding of microbiota-immune system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…For example, mAb 40A6 showed both high-binding and low-binding interactions with glycans from Proteus penneri, Proteus mirabilis, Shigella boydii, Salmonella Typhimurium, and various strains of Escherichia coli . These findings support the conclusion that microbial surface glycans are common targets of microbiota-reactive IgAs (15, 48). …”
Section: Microbiota-reactive Antibodies Bind a Diverse Subset Of Commsupporting
confidence: 87%
“…For example, mAb 40A6 showed both high-binding and low-binding interactions with glycans from Proteus penneri, Proteus mirabilis, Shigella boydii, Salmonella Typhimurium, and various strains of Escherichia coli . These findings support the conclusion that microbial surface glycans are common targets of microbiota-reactive IgAs (15, 48). …”
Section: Microbiota-reactive Antibodies Bind a Diverse Subset Of Commsupporting
confidence: 87%
“…The hybridoma 225.4, which produces IgA specific for a capsular polysaccharide locus of B. thetaiotaomicron, decreased bacterial epitope expression, the fitness of the bacterium in vivo, and the level of host mucosal innate immune activation measured by transcriptional analysis of mucosal biopsies [47]. By contrast, a different hybridoma -260.8 -did not decrease LPS O-antigen epitope production, nor was the bacterial population density affected [48]. The technical challenges of creating such defined animal models have limited the number of monoclonal antibodies analysed in this way to date, although the results give us an insight Review Trends in Immunology xxx xxxx, Vol.…”
mentioning
confidence: 68%
“…Binding of sIgA to bacteria may contribute to mucosal biofilm formation, which serves as a barrier to pathogen adherence 103 . Gnotobiotic studies with Rag1 knockout mice (which effectively have no adaptive immune system) showed that experimental coating of B. thetaiotaomicron with sIgA reduces microbial fitness but also leads to reduced inflammatory signaling and changes to bacterial gene expression 5,104 . Through these mechanisms, sIgA mediates homeostasis between the host and the microbiota, as well as potential pathogens at mucosal surfaces.…”
Section: Mechanisms Responsible For Gut Biogeographymentioning
confidence: 99%